Iowa Gambling Task Performance Prospectively Predicts Changes in Glycemic Control among Adolescents with Type 1 Diabetes. (9th January 2017) - Suchy, Yana; Queen, Tara L.; Huntbach, Bryce; Wiebe, Deborah J.; Turner, Sara L.; Butner, Jonathan; Kelly, Caitlin S.; White, Perrin C.; Murray, Mary; Swinyard, Michael; Berg, Cynthia A.
Abstract: Objectives: Good glycemic control is an important goal of diabetes management. Late adolescents with type 1 diabetes (T1D) are at risk for poor glycemic control as they move into young adulthood. For a subset of these patients, this dysregulation is extreme, placing them at risk for life-threatening health complications and permanent cognitive declines. The present study examined whether deficiency in emotional decision making (as measured by the Iowa Gambling Task; IGT) among teens with T1D may represent a neurocognitive risk factor for subsequent glycemic dysregulation.Methods: As part of a larger longitudinal study, a total of 241 high-school seniors (147 females, 94 males) diagnosed with T1D underwent baseline assessment that included the IGT. Glycated hemoglobin (HbA1c), which reflects glycemic control over the course of the past 2 to 3 months, was also assessed at baseline. Of the 241, 189 (127 females, 62 males, mean age=17.76, mean HbA1c=8.11) completed HbA1c measurement 1 year later.Results: Baseline IGT performance in the impaired range (per norms) was associated with greater dysregulation in glycemic control 1 year later, as evidenced by an average increase in HbA1c of 2%. Those with normal IGT scores (per norms) exhibited a more moderate increase in glycemic control, with an HbA1c increase of 0.7%. Several IGT scoring approaches were compared, showing that the total scores collapsed across all trials was most sensitive to change in glycemic control.Conclusions: IGT assessment offers promise as a tool for identifying late adolescents at increased risk for glycemic dysregulation. ( JINS, 2017, 23, 204–213)